The Great Revival : beginnings of the Bible belt - Boles, John B. (Religion in the South, 1996)
Drawing upon the religious writings of southern evangelicals, John Boles asserts that the extraordinary crowds and miraculous transformations that distinguished the South's First Great Awakening were not simply instances of emotional excess but the expression of widespread and complex attitudes toward God. Converted southerners were starkly individualistic, interested more in gaining personal salvation in a hopelessly evil world than in improving society. As Boles shows in this landmark study, the effect of the Revival was to throw over the region a conservative cast that remains dominant in c.